PVC Polymeric Membranes Coated Graphite Electrodes Based on Molecularly Imprinted Polymers for the Selective Determination of Glibenclamide - M. Yassen, Hamsa; I. Abdulla, Najwa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Graphite coated electrodes (GCE) based on molecularly imprinted polymers were fabricated for the selective potentiometric determination of Glibenclamide (Glb). The molecularly imprinted (MIP) and nonimprinted (NIP) polymers were synthesized by radical bulk polymerization using (Glb.) as a template, acrylic acid (AA) and acrylamide (AAm) as monomers, ethylene glycol dimethacrylate (EGDMA) as a cross-linker and benzoyl peroxide (BPO) as an initiator. The imprinted membranes and the non-imprinted membranes were prepared using dioctyl phthalate (DOP) and Dibutylphthalate (DBP) as plasticizers in PVC matrix. The membranes were coated on graphite electrodes. The MIP electrodes using (AA) and (AAm) showed a near nernstian response with slopes of -51.5±0.5and 57.8±0.1mV/decade, correlation coefficient (r2) 0.9762 and 0.9992, a linear response for a concentration range of (1.0×10-4- 1.0×10-2) M and (1.0×10-5- 1.0×10-3) M and detection limit of 1.0×10-4M and 1.0×10-5M respectively. The response time of the prepared electrodes was less than 30 seconds. The electrode responses were stable in a pH range (2-4). The electrodes could be successfully used within (1and 6) weeks respectively without any drift. The sensors exhibited good selectivity over a wide range of interference. The most effective electrode was used to determine the concentration of (Glb.) in some pharmaceutical formulations.